2012
DOI: 10.1038/gim.0b013e31822e578f
|View full text |Cite
|
Sign up to set email alerts
|

Personal privacy, public benefits, and biobanks: a conjoint analysis of policy priorities and public perceptions

Abstract: Purpose: To assess the public's perception of biobank research and the relative importance they place on concerns for privacy and confidentiality, when compared with other key variables when considering participation in biobank research.methods: Conjoint analysis of three key attributes (research focus, research beneficiary, and privacy and confidentiality) under conditions of either blanket or specific consent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 26 publications
(29 reference statements)
3
44
0
Order By: Relevance
“…In relation to research priorities, people expressed an expectation that biobanks should prioritise disease focus, concentrate on a broad range of diseases and not conduct research that is morally questionable. This supports the work of Pullman et al (2012), who found that an important reason given for choosing not to participate in biobank research was the type of research focus (i.e. stigmatised diseases), and more general research that demonstrates that people are concerned about future use of their donated samples in morally questionable research (Lemke et al, 2010).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In relation to research priorities, people expressed an expectation that biobanks should prioritise disease focus, concentrate on a broad range of diseases and not conduct research that is morally questionable. This supports the work of Pullman et al (2012), who found that an important reason given for choosing not to participate in biobank research was the type of research focus (i.e. stigmatised diseases), and more general research that demonstrates that people are concerned about future use of their donated samples in morally questionable research (Lemke et al, 2010).…”
Section: Discussionsupporting
confidence: 72%
“…privacy, type of condition studied and who benefits) within the one study (e.g. Pullman et al, 2012). Between-group study comparisons are also difficult, given the lack of standardisation across the operationalisation of constructs (e.g.…”
Section: Identifying Public Expectations Of Genetic Biobanksmentioning
confidence: 99%
See 1 more Smart Citation
“…Although concerns about privacy protection in genomic research exist, they do not influence public's willingness to consent and were rated least important. 38,46 Furthermore, in quantitative studies with patients and the public, respondents expressed a great sense of trust in non-profit or publicly funded research organizations as well as in doctors, hospitals and university-based researchers. However, they had little or no trust in for-profit organizations, insurance companies and the pharmaceutical industry.…”
mentioning
confidence: 99%
“…Many countries and organizations are investing in biobanks to acquire large population datasets from which to improve characterizing of patients and their diseases. These are important resources for improving drug discovery [14,20]. Network pharmacology [21] aims to bring together these and other sophisticated international databases relevant to genetic and acquired mechanisms for disease [22], pharmacological pathways, candidate drugs, and population data describing important variants among individuals in disease patterns, drug handling and responsiveness [23,24].…”
Section: New Research Approachesmentioning
confidence: 99%